2018
DOI: 10.7577/hrer.2852
|View full text |Cite
|
Sign up to set email alerts
|

The indigenous Sami citizen and Norwegian national identity: tensions in curriculum discourses

Abstract: The paper explores citizenship positions for the Sami as citizen in the overarching policy document for the Norwegian school. Informed by the perspective that policy documents hold discursive productivity in the Foucauldian sense, this document is regarded as vital for locating normative cultural ideals. The analysis points to three discourses: indigeneity, multiculturalism and the common Norwegian cultural heritage perspective. Although the analysis suggests that there is a variety of possible citizenship ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…Moreover, researchers find that the curriculum is often developed from the majority perspectives, with few references to indigenous knowledge (Apple & Buras, 2006;Eriksen, 2018;Gruenewald, 2003;Olsen & Andreassen, 2018). While the Norwegian curriculum regarding Sámi issues, has gone from being ignorant to aiming for inclusivity (Hirvonen & Keskitalo, 2004;Olsen, 2019), indigenous Sámi perspectives are underdeveloped, and regional and contextual diversity is lacking.…”
Section: Researchers Found Diverging Curricular Discourses Concerning...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, researchers find that the curriculum is often developed from the majority perspectives, with few references to indigenous knowledge (Apple & Buras, 2006;Eriksen, 2018;Gruenewald, 2003;Olsen & Andreassen, 2018). While the Norwegian curriculum regarding Sámi issues, has gone from being ignorant to aiming for inclusivity (Hirvonen & Keskitalo, 2004;Olsen, 2019), indigenous Sámi perspectives are underdeveloped, and regional and contextual diversity is lacking.…”
Section: Researchers Found Diverging Curricular Discourses Concerning...mentioning
confidence: 99%
“…These constraints indicate that students must make a tremendous effort to learn the language, an effort the educational system does not sufficiently accommodate. The Norwegian colonial position reinforces the insignificance of Sámi history, knowledge, and practices (see Eriksen, 2018;Hoëm, 2010;Kumashiro, 2000;Maldonado-Torres, 2004;Morgan, 2003). Because of this, education downgrades Sámi worldviews and the aim to strengthen Sámi identity, which causes an insufficient The lack of sufficiency in Sámi language is a major issue among students:…”
Section: Frøy Expressed: "I Don't Know If I Would Say I'm Sámi It Dep...mentioning
confidence: 99%
“…Suomessa ei ole kaikkia koskevaan opetussuunnitelman osaan sisällytetty saamelaistietoa. Esimerkiksi Norjassa opetussuunnitelmaan on saamelaistietoa lisätty selvemmin, vaikka siinäkin on edelleen kehitettävää (Eriksen 2018).…”
Section: Episteeminen Strateginen Ja Eettinen Tietämättömyysunclassified
“…Words such as we , us , and our are widely used about the majority society, whereas the Indigenous group is referred to as them (Smith, 2012, p. 37). Research published in Norway has shown that textbook representations of Indigenous peoples have tended toward the stereotypical rather than encouraging insight into the diversity of Indigenous ways of living and thinking (Brown & Habegger‐Conti, 2017; Eriksen, 2018; Lund, 2016; Olsen, 2017). One‐sided representations may reduce cultures to specific, often exotic characteristics rather than looking at present‐day ways of living and ways of thinking (Brown & Habegger‐Conti, 2017).…”
Section: Intercultural Competence and Teaching About Indigenous Peoplesmentioning
confidence: 99%
“…This discussion should happen before pupils start work with the topic that is the focus of the teaching module. This is necessary to avoid a “whitestreaming” of the content, that is, a bias toward White and majority history and cultures to the detriment of minority perspectives (Eriksen, 2018, p. 36).…”
Section: Practical Approaches For Teaching About Indigenous Peoples I...mentioning
confidence: 99%